Smoking Cessation Experience in Indonesia: Does the Non-smoking Wife Play a Role? - Ayuningtyas, Dyah A.; Tuinman, Marrit A.; Prabandari, Yayi S.; Hagedoorn, Mariët (Frontiers in Psychology, 2021)
Objective: Over 63% of Indonesian men are smokers, and smoking has long been a part of Indonesian culture and of the concept of masculinity in Indonesian culture. Given the pro-smoking environment, we were interested in examining why smokers would willingly quit and whether their wives played a role in their quitting process, as social factors are mentioned second most often as a reason for quitting smoking. Design: In-depth interviews. Method: We interviewed eleven couples (N = 22) – ex-smoking husbands and non-smoking wives – in Yogyakarta, Indonesia. The data were analysed using the thematic analysis approach. Results: Four themes were discussed: (1) reasons for stopping smoking, (2) the process of quitting smoking, (3) the wives’ attitudes towards smoking, and (4) the families’ attempts to make the (ex-)smokers quit. The most commonly cited reasons for quitting were family and personal motivation. The (ex-)smokers preferred to quit without assistance and in private. The wives’ attitude toward smoking ranged from dislike to tolerance, and most did not know when their husbands were trying to quit. Both husbands and wives reported that the wives did not influence the smoking cessation process. Conclusion: Indonesian ex-smokers often had multiple reasons for quitting smoking. The process was often difficult and kept private. While wives could not influence the cessation process, they provided support and could institute a smoking ban in the house.